Quantitative evaluation of integrated neuroendocrine and immune responses to chronic stress in rats male - Іlona S Polovynko; Lyubomyr М Zajats; Walery Zukow; Roman I Yanchij; Igor L Popovych (Kazimierz Wielki University, 2016)
Polovynko Іlona S, Zajats Lyubomyr М, Zukow Walery, Yanchij Roman I, Popovych Іgor L. Quantitative evaluation of integrated neuroendocrine and immune responses to chronic stress in rats male. Journal of Education, Health and Sport. 2016;6(8):154-166. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60023 http://ojs.ukw.edu.pl/index.php/johs/article/view/3745       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016.     QUANTITATIVE EVALUATION OF INTEGRATED NEUROENDOCRINE AND IMMUNE RESPONSES TO CHRONIC STRESS IN RATS MALE   Іlona S Polovynko1, Lyubomyr М Zajats1, Walery Zukow2, Roman I Yanchij3, Іgor L Popovych3   1Department of Pathophysiology, National Medical University, Ivano-Frankivs'k, Ukraine   patfisiology@ifnmu.edu.ua   VLDC@meta.ua 2Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland   w.zukow@ukw.edu.pl 3Department of Immunophysiology, OO Bohomolets' Institute of Physiology NAS, Kyiv, Ukraine   i.popovych@biph.kiev.ua     Abstract Background. Previously we have been analysed neuro-endocrine-immune relationships by chronic restraint stress at male rats. The purpose of this study - to carry out integrated quantitative estimation of neuroendocrine and immune responses to chronic restraint stress at male rats. Material and research methods. The experiment is at 50 white male rats. Of these 10 animals not subjected to any influences and 40 within 7 days subjected to moderate stress by daily 30-minute immobilization. The day after the completion of stressing in rats of both groups determined parameters of heart rate variability, urinary excretion of 17-ketosteroids, plasma levels of corticosterone, testosterone, thyroxine and triiodothyronine as well as sodium, potassium, calcium and phosphates. The same portion of the blood immunological parameters were determined by tests I and II levels of WHO. The spleen and thymus did smears for counting spleno- and thymocytograms. In sections of the adrenal glands was measured the thickness of glomerular, fascicular, reticular and medullar zones. Results. The method of discriminant analysis found that distinctive endocrine signs of chronic stress is increasing the thickness of Fasciculary Zone whereas decreasing thickness of Glomerulary Zone of Adrenal Cortex as well as plasma (Ca/P)0,5 ratio as Parathyrine Activity. Other signs of chronic stress such as increasing plasma levels Corticosterone, Testosterone and Triiodethyronine, Sympathetic tone, Heart Rate and thickness of Reticular Zone of Adrenals as well as decreasing Vagal Tone and plasma (Na/K)0,5 ratio as Mineralocorticoid Activity currently not in the discriminant model. Canonical Neuroendocrine Roots for Intact and Stressed Males Rats averages +0,99±0,40 and -0,25±0,15 respectively (Squared Mahalanobis Distance=1,61; F=3,76; p=0,017). Among the parameters of Immunity characteristic of chronic stress appeared to increase Thymus Massa Index, level in Thymocytogram of Macrophages and Reticulocytes, in Splenocytogram of Macrophages and Eosinophils, while Monocytes in Leukocytogram of Blood as well as Entropy of Leukocytogram and Splenocytogram whereas decrease both Intensity and Activity of Phagocytose by Neutrophils, levels of Endotheliocytes in Thymocytogram, Neutrophils in Splenocytogram, NK-Lymphocytes, Stub Neutrophils and Basophils in Leukocytogram. Canonical Immune Roots for Intact and Stressed Males Rats averages -3,41±0,40 and +0,85±0,15 respectively (Squared Mahalanobis Distance=19,0; F=5,44; p<10-4). Canonical correlation between Neuroendocrine and Immune parameters is very strong: R=0,976; χ2(297)=432; p<10-6. Conclusion. The components of the autonomic nervous, endocrine and immune systems interact closely within the triune neuroendocrine-immune complex and changing them exposed to integrated evaluation. The author's approach can be used to quantify the integrated assessment of intensity of stress factors and to integral assessing the effectiveness of stresslimiting factors.   Keywords: chronic stress, autonomic regulation, adaptive hormones, adrenals, thymocytogram, splenocytogram, leukocytogram and immunocytogram of blood, relationships, male rats.